1978
DOI: 10.1071/ar9780885
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Boophilus microplus (Canestrini) in different breeds of cattle

Abstract: Resistance to the cattle tick Boophilus microplus was assessed in heifer herds of various breeds of beef and dairy cattle in spring and summer in Queensland. All cattle had had tick experience before assessment. Resistance levels were determined as the percentage of larval ticks that failed to survive to maturity following infestations with c. 20,000 larvae. Bos indicus Brahman beef cattle were the most resistant (99%), followed by B. indicus × B. taurus (95–97%) and B. taurus British cattle (85%). In the dair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
1
18

Year Published

1985
1985
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(105 citation statements)
references
References 0 publications
6
77
1
18
Order By: Relevance
“…Furthermore, about 16.67% of the Canchim x Nelore heifers were included in the > 98% to ≤ 99% TM group, which also included 18.75% of the Angus x Nelore and 31.25% of the Simmental x Nelore heifers. Based on the classification of Utech et al (1978) all (100%) of the Nelore heifers and the Canchim x Nelore heifers would be considered highly tick-resistant while only 87.5% of the Angus x Nelore heifers and 93.75% of the Simmental x Nelore heifers would be considered highly tick-resistant, the remaining percentage of Angus x Nelore heifers (12.5%) and Simmental x Nelore heifers (6.25%) being moderately tickresistant. Since Canchim x Nelore heifers have, on average, a higher proportion of B. indicus zebu genes the higher percentage of high tick-resistance shown by these heifers as compared to Angus x Nelore and Simmental x Nelore heifers, with a relatively low percentage of B. indicus genes, was to be expected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, about 16.67% of the Canchim x Nelore heifers were included in the > 98% to ≤ 99% TM group, which also included 18.75% of the Angus x Nelore and 31.25% of the Simmental x Nelore heifers. Based on the classification of Utech et al (1978) all (100%) of the Nelore heifers and the Canchim x Nelore heifers would be considered highly tick-resistant while only 87.5% of the Angus x Nelore heifers and 93.75% of the Simmental x Nelore heifers would be considered highly tick-resistant, the remaining percentage of Angus x Nelore heifers (12.5%) and Simmental x Nelore heifers (6.25%) being moderately tickresistant. Since Canchim x Nelore heifers have, on average, a higher proportion of B. indicus zebu genes the higher percentage of high tick-resistance shown by these heifers as compared to Angus x Nelore and Simmental x Nelore heifers, with a relatively low percentage of B. indicus genes, was to be expected.…”
Section: Resultsmentioning
confidence: 99%
“…This was to be expected because the environmental conditions in our study were more controlled than in natural infestations with long periods between counts during which there can be physiological changes in cattle, climate and pasture. Utech et al (1978) divided tick-resistance in cattle into the following tick-mortality (TM) classes: > 98% TM, highly tick-resistant cattle; 95.1% to 98% TM, moderately tick-resistant; 90% to 95% TM, low tickresistance; and < 90% TM, very low tick-resistance. The observed TM based on the mean PRT ij values of the four infestations (Table 3) shows that a TM above 99% occurred in the following percentage of heifers: 100% for Nelore; 83.33% for Canchim x Nelore; 68.75% for Angus x Nelore; and 62.5% for Simmental x Nelore.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research had shown that cattle of the Jersey and Illawarra Shorthorn breeds show lower tick burdens than other taurine cattle but not enough to be called tick resistant (Utech et al 1978). In the Jersey, the mechanism appears to be a form of hypersensitivity.…”
Section: Cattle Samplesmentioning
confidence: 99%
“…According to Utech et al (1978) high levels of host resistance to ticks are primarily associated with zebu cattle, but a proportion of resistant individuals can occur in all breeds. Hence the objective of this study was to assess total tick burden difference, which is one of an indicator for tick resistance differences, of indigenous and Holstein-crosses (50%) in Kokatie, area.…”
Section: Introductionmentioning
confidence: 99%